High-Throughput Immunogenetics Reveals a Lack of Physiological T Cell Clusters in Patients With Autoimmune Cytopenias - Simnica, Donjete; Schliffke, Simon; Schultheiß, Christoph; Bonzanni, Nicola; Fanchi, Lorenzo F.; Akyüz, Nuray; Gösch, Barbara; Casar, Christian; Thiele, Benjamin; Schlüter, Janina; Lohse, Ansgar W.; Binder, Mascha (Frontiers in Immunology, 2019)
Autoimmune cytopenias (AIC) such as immune thrombocytopenia or autoimmune hemolytic anemia are claimed to be essentially driven by a dysregulated immune system. Using next-generation immunosequencing we profiled 59 T and B cell repertoires (TRB and IGH) of 25 newly diagnosed patients with primary or secondary (lymphoma-associated) AIC to test the hypothesis if these patients present a disease-specific immunological signature that could reveal pathophysiological clues and eventually be exploited as blood-based biomarker. Global TRB and IGH repertoire metrics as well as VJ gene usage distribution showed uniform characteristics for all lymphoma patients (high clonality and preferential usage of specific TRBV- and TRBJ genes), but no AIC-specific signature. Since T cell immune reactions towards antigens are unique and polyclonal, we clustered TCRβ clones in-silico based on target recognition using the GLIPH (grouping of lymphocyte interactions by paratope hotspots) algorithm. This analysis revealed a considerable lack of physiological T cell clusters in patients with primary AIC. Interestingly, this signature did not discriminate between the different subentities of AIC and was also found in an independent cohort of 23 patients with active autoimmune hepatitis. Taken together, our data suggests that the identified T cell cluster signature could represent a blood biomarker of autoimmune conditions in general and could be helpful in the differential diagnosis of intricate cases with unclear presentation especially if their autoimmune etiology is uncertain.